Birthing a Graphic Archive of Memory: Re-Viewing the Refugee Experience in Thi Bui's The Best We Could Do. (13th November 2020) - Oh, Stella
Abstract: The Vietnam War is the topic of books, comics, documentaries, films, and television shows. Contrary to popular filmic and literary representations of the Vietnam War, which feature violence and militant hypermasculinity, Thi Bui's The Best We Could Do: An Illustrated Memoir (2017) weaves a tapestry of stories about the Vietnam War through memories of her family members. Rather than reiterating a shibboleth of masculine struggle and American exceptionalism during the war, Bui's narrative centers on women, specifically their experiences with birthing and motherhood. Her graphic novel offers us an alternative lens to view the Vietnam War and the experiences of those whose stories were often excluded. The Best We Can Do illustrates memories of women and families commonly disregarded as unimportant and affirms their importance in understanding history and identities shaped by such exclusions. In mapping bodies and their various connections and separations to the nation and to each other, Bui invokes a new archive of memory in which the female body becomes a site for reframing the discourse of the Vietnam War.